OPTIMIZATION OF MORAL AND RELIGIOUS DEVELOPMENT IN EARLY CHILDREN THROUGH THE GAME METHOD - Ahmad Rifai; Husin; Rahmadiati; Abdul Rashid bin Abdul Aziz (International Forum of Researchers and Lecturers, 2022)
Optimization is an effort to maximize activities so as to realize the desired profit. The words morality and religion are often discussed among the people, wherever and whenever. Moral and religious development in early childhood can be interpreted as psychological changes experienced by early childhood related to their ability to understand and perform good behavior as well as understand and avoid bad behavior based on religious teachings that are believed. There are 3 types of games that can be used in the game method, 1) clap game, 2) singing, 3) game tools. This study aims to find out how to optimize moral and religious development in early childhood through the game method. This type of research uses library research or library research which makes library materials in the form of books, scientific magazines, documents and other materials that can be used as a reference source in this research. The results of the study show that this game method can be used by parents or early childhood educators because this method easily stimulates existing developments in children, both moral development and religious development. moral and religious development in children. Also using the learning game method will be more fun.